Concomitant use of clopidogrel and proton-pump inhibitor: a reality check. (April 2010) - Banerjee, Subhash; Zankar, Ahmad; Weideman, Rick; Little, Bertis; Brilakis, Emmanouil S
There are emerging reports supporting the fact that proton-pump inhibitors competitively inhibit the metabolism of clopidogrel to its active metabolite and diminish its clinical efficacy, especially in patients on long-term dual antiplatelet therapy. In this article, we examine the current evidence and provide interpretation of the results along with practical recommendations for healthcare providers.